2017
DOI: 10.1016/j.ymthe.2016.10.014
|View full text |Cite
|
Sign up to set email alerts
|

CRISPR/Cas9-Induced (CTG⋅CAG) n Repeat Instability in the Myotonic Dystrophy Type 1 Locus: Implications for Therapeutic Genome Editing

Abstract: Myotonic dystrophy type 1 (DM1) is caused by (CTG⋅CAG)n-repeat expansion within the DMPK gene and thought to be mediated by a toxic RNA gain of function. Current attempts to develop therapy for this disease mainly aim at destroying or blocking abnormal properties of mutant DMPK (CUG)n RNA. Here, we explored a DNA-directed strategy and demonstrate that single clustered regularly interspaced short palindromic repeats (CRISPR)/Cas9-cleavage in either its 5′ or 3′ unique flank promotes uncontrollable deletion of l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
127
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3
2

Relationship

1
9

Authors

Journals

citations
Cited by 110 publications
(137 citation statements)
references
References 83 publications
7
127
3
Order By: Relevance
“…Technologies that engage the DM1-linked repeat expansion on both the DNA and RNA levels have been investigated. Although excision of these large tracts in DNA followed by repair in their absence is possible (9), this genome engineering approach has not yet been realized with high efficiency. ASOs provide means to engage pathogenic RNAs directly but must be continuously re-administered for life and have experienced poor biodistribution in muscle in the clinic.…”
Section: Main Textmentioning
confidence: 99%
“…Technologies that engage the DM1-linked repeat expansion on both the DNA and RNA levels have been investigated. Although excision of these large tracts in DNA followed by repair in their absence is possible (9), this genome engineering approach has not yet been realized with high efficiency. ASOs provide means to engage pathogenic RNAs directly but must be continuously re-administered for life and have experienced poor biodistribution in muscle in the clinic.…”
Section: Main Textmentioning
confidence: 99%
“…Reconstitution of these DNA-targeting systems in eukaryotic cells has supported powerful applications in genome editing and other DNA-level manipulations (Sheridan, 2017; Yu et al, 2017). A recent study demonstrated that MREs can be excised from DNA using genome engineering techniques (van Agtmaal et al, 2017), although simultaneous induction of a pair of double-stranded breaks flanking the MRE followed by DNA repair in the absence of the repeat has not been realized with sufficient efficiency. In contrast to RNA-directed systems, genome editing features the risk of permanent, off-target edits to DNA (Schaefer et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Multiple groups have successfully edited genomes in cell and animal models of disease. Some have directly applied these approaches to microsatellite expansion diseases to remove the expanded repeat tract 40 or cause somatic instability leading to repeat contraction 41 . However, challenges remain to ensure both efficient and specific cleavage activity across multiple cells and tissues of the body.…”
Section: Discussionmentioning
confidence: 99%